Work Environment, Competence With Motivation as a Mediating Variable on Employee Performance: (Case Study On Employees of the Indramayu District Health Office) - Ibnu Baihaqi; Fadillah Rayhan; Fiky Darmawan; Ade Solahudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the work environment, competence, work motivation, and employee performance. In addition, it also aims to see work motivation as a mediation between these relationships. The Indramayu Regency Health Office served as the study site, and questionnaires were distributed to gather primary data. Saturated sampling, which involves drawing samples from the whole population, is the method utilized here. The Indramayu Regency Health Office staff constituted the 100-person sample for this research. The Structural Equation Model (SEM) was used to evaluate this data, employing data analysis approaches based on Partial Least Square (PLS). The difference between this research and previous research is in the object, population and research sample, research period, measuring instruments and research results. This research has large practical implications, especially in the context of human resource management in the public sector, especially at the Indramayu District Health Service. The findings from this research can help managers or leaders optimize their employees' performance by improving a conducive work environment, developing employee competencies and high motivation. By knowing that motivation can act as a mediating variable between the work environment and work competence and employee performance, managers can design policies or programs that are more oriented to employee needs and motivation.